Literature review on mediation/sulh in resolving child custody disputes in the Syariah Court in Malaysia - Abdul Hak, Nora; Mansor, Ahmad Mukhlis; Che Soh @ Yusoff, Roslina (2019)
In previous studies conducted, mediation (sulh) has been reported to be a successful mechanism in reducing the backlog of cases and able to lessen cases or disputes being brought to court trial. However, based on a recent statistic especially, in cases of child disputes in the Syariah Courts throughout Malaysia, it shows that less than 50% of these cases have been settled at the sulh process. Furthermore, the statistic also reveals that 4,826 out of 15,243 cases of sulh in child custody disputes cannot proceed due to non-attendance of parties to the sulh proceeding. This has resulted in the cases being brought to the court for trial instead of being settled through sulh process. It is suggested that the mechanisms and the implementation of sulh in the Syariah Court are insufficient in dealing with the child custody issues. Moreover, it is also suggested that the current legal frameworks are insufficient to make sulh session a success. Therefore, as a preliminary study to the above issue, a literature review study on the topic has been conducted and it shows that there is insufficient research/writing specifically on the practice of sulh in child custody disputes in Malaysia. The aim of this paper is to discuss and analyse all the relevant literatures on the topic in order to have a better understanding of the role and function of sulh/mediation in helping the parties resolving their child custody dispute. The methodology adopted is a library study to collect information, data and theories involved. Then, the data were analyzed by using content analysis method.